2009
DOI: 10.1111/j.1745-459x.2009.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP OF PROP (6‐N‐PROPYLTHIOURACIL) TASTER STATUS WITH THE BODY MASS INDEX AND FOOD PREFERENCES OF FILIPINO ADULTS

Abstract: The study determined the 6‐n‐propylthiouracil (PROP) status of Filipino adults and how it relates to their body mass indices (BMI) and food preferences. Self‐reported food preference checklists were administered to 100 male and female adults aged 18–60, classified according to BMI. Increasing concentrations of PROP and NaCl solutions were rated in labeled magnitude scale to establish the PROP taster status of the selected respondents. The Filipino adult respondents were composed of 12% nontasters, 45% medium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 74 publications
(225 reference statements)
5
20
2
Order By: Relevance
“…Indeed, PAV/PAV individuals perceive the bitterness from cruciferous vegetables, which contain glucosinolates -a class of anti-thyroid compounds that include the thiourea moiety (N-C@S) common to PROP and PTC -more intensely than those with the AVI/AVI genotype (Sandell & Breslin, 2006). A number of studies have reported lower preference for cruciferous vegetables and other bitter foods and beverages, including bitter green vegetables, coffee, grapefruit juice, tonic water, horseradish and cabbage (Dinehart et al, 2006;Drewnowski et al, 1997Drewnowski et al, , 2000Drewnowski, Ahlstrom-Henderson, Levine, & Hann, 1999;Duffy et al, 1999;Lanier et al, 2005;Villarino et al, 2009). The current work suggests an inverse relationship between PROP intensity and liking for some of these food items.…”
Section: Pts and Propmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, PAV/PAV individuals perceive the bitterness from cruciferous vegetables, which contain glucosinolates -a class of anti-thyroid compounds that include the thiourea moiety (N-C@S) common to PROP and PTC -more intensely than those with the AVI/AVI genotype (Sandell & Breslin, 2006). A number of studies have reported lower preference for cruciferous vegetables and other bitter foods and beverages, including bitter green vegetables, coffee, grapefruit juice, tonic water, horseradish and cabbage (Dinehart et al, 2006;Drewnowski et al, 1997Drewnowski et al, , 2000Drewnowski, Ahlstrom-Henderson, Levine, & Hann, 1999;Duffy et al, 1999;Lanier et al, 2005;Villarino et al, 2009). The current work suggests an inverse relationship between PROP intensity and liking for some of these food items.…”
Section: Pts and Propmentioning
confidence: 97%
“…Additionally, three separate food groupings were created: Food Groups, Orosensory Groups, and Correlation Groups. Food Groups were based on food type (Villarino et al, 2009), which included the main groups (and sub-groups) Dairy (yogurt, milk, frozen/ sweet dairy, cream), Meat (poultry, beef, pork, hamburger/hot dog/sausage, fish, seafood, other), Grain (rice, pasta, breads, hot cereal, cold cereal, crackers), Vegetable (cooked vegetables, raw vegetables), Fruit (cooked fruits, raw fruits, preserved fruits), Dessert (cookies, bars, cakes, donuts, pies, pudding, other), Eggs, Nuts, Curry, Horseradish, and Wasabi. Orosensory Groups were created through the identification and grouping of a sub-set of foods that share a predominant taste, texture, or chemesthetic quality.…”
Section: Food Liking and Food Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The food preferences checklist used included 88 food items (Villarino, Fernandez, Alday, & Cubelo, 2009) which were representative of the various food groups given in the Philippine Food Composition Tables (FCT FNRI, 1997) and different taste modalities. The checklist had a 9-point hedonic scale to rate the respondents' liking or disliking for each item.…”
Section: Food Preference Checklistmentioning
confidence: 99%
“…Oronasal sensitivity varies greatly among individuals and is purported to affect food consumption behaviour and subsequently a range of health and disease outcomes (Stewart, et al, 2010, Villarino, et al, 2009, Ullrich, et al, 2004. Many factors contribute to this individual variation, such as age, gender, ethnic origin and different phenotypes (Mojet, et al, 2003, Mojet, Leshem, et al, 2003, Hirokawa, et al, 2006, Pickering, et al, 2010, Lim, et al, 2008.…”
Section: Introductionmentioning
confidence: 99%